Thermodynamic properties of fluids & fluid mixtures. Abdulagatov, I.M.; Rabinovich, V.A.; Dvoryanchikov, V.I. Begell House Inc. Publishers New York 1999. 350 p. - Ulco de Ponce, Vilma (2000)
El artículo no presenta resumen.